Impact of rural credit facilities of Micro-Finance Banks on poverty alleviation – the Nigeria experience (2015)
The study focused on the impact of rural credit facilities of Micro- Finance Banks (MFBs) on poverty alleviation in Nigeria from 2005-2012. The overall objective of the study was to assess the impact of rural credit facilities of MFBs on rural financial markets and the implication on the rural economy and poverty alleviation. Multi–stage random sampling technique was utilized in the selection of rural MFBs and household respondents. In the first stage, 3 states – Anambra, Imo and Enugu were randomly selected from the 5 states that make the South Eastern Nigeria. Furthermore, from the 77 rural–based MFBs in South Eastern Nigeria, 27 were randomly selected from 27 communities. Finally, 10 household head respondents were selected from each of the 27 communities, making a total of 270 respondents, out of which 265 were successfully administrated with instruments of data collection. Data for the study were collected from primary and secondary sources. Primary data were collected from the respondents with the aid of interview schedule and questionnaire while secondary data came largely from annual financial statements of MFBs as collated and published in statistical bulletins of the Central Bank of Nigeria. Analysis of data collected was done with Multinomial Logistic Regression Model and descriptive statistics such as means and percentages. The study showed, among others, that deposits mobilized from rural communities by MFBs were siphoned out of the communities by way of fixed deposits with commercial banks usually located outside the communities, thereby defeating the sole idea of financial intermediation within the communities. The paper concluded that in spite of modest impact of rural credit facilities from MFBs with respect to deposit mobilization, wide areas for improvement still exist in relation to participation of women in credit facilities, among others. The study recommended the institution of gender equalization policies that would create incentives for increased lending to women.